Sepiolite-Hydrogels: Synthesis by Ultrasound Irradiation and Their Use for the Preparation of Functional Clay-Based Nanoarchitectured Materials - Ruiz-Hitzky, Eduardo; Ruiz-García, Cristina; Fernandes, Francisco M.; Lo Dico, Giulia; Lisuzzo, Lorenzo; Prevot, Vanessa; Darder, Margarita; Aranda, Pilar (Frontiers in Chemistry, 2021)
Sepiolite and palygorskite fibrous clay minerals are 1D silicates that exhibit unique textural and structural characteristics useful for diverse applications including rheological additives. Here we report on the ability of grinded sepiolite to generate highly viscous and stable hydrogels by sonomechanical irradiation (ultrasounds). Adequate drying of such hydrogels leads to low-density xerogels that show an elevated degree of fibers disaggregation compared to the starting sepiolite, whose fibers are agglomerated as bundles. These xerogels show comparable rheological properties to commercially available defibrillated sepiolite products, which by re-dispersion in water under high-speed shear can generate high viscosity hydrogels minimizing the syneresis phenomena. These colloidal systems are very interesting as they can be used as stabilizers of many diverse compounds as well as nano-/micro-component materials leading to the production of a large variety of composites and nano/micro-architectured solids. In this context, we report here various examples showing how colloidal routes based on sepiolite hydrogels can be used to obtain new heterostructured functional materials, in the present case based on their assembly to solids of diverse topology and composition such as 2D and 1D kaolinite and halloysite aluminosilicates, as well as to the 2D synthetic Mg,Al-layered double hydroxide (LDH).